Helicobacter pylori infection promotes M1 macrophage polarization and gastric inflammation by activation of NLRP3 inflammasome via TNF/TNFR1 axis - Fei Xiao; Sihai Chen; Leyan Li; Xinbo Xu; Huan Wang; Huajing Ke; Cong He; Chuan Xie; Xidong Wu; Jianping Liu; Yong Xie; Nonghua Lü; et al. (2025)
Macrophages play a crucial role in chronic gastritis induced by the pathogenic Helicobacter pylori (H. pylori) infection. NLRP3 inflammasome has emerged as an important component of inflammatory processes. However, the molecular mechanism by which H. pylori infection drives NLRP3 inflammasome and macrophages activation remains unclear. Human gastritis tissues were collected for clinical significance of NLRP3. Infection with H. pylori was performed using in vitro and in vivo models. Bone marrow-derived macrophages (BMDMs) from wild-type (WT), Nlrp3-knockout (KO) and Tnfr1-KO mice were infected with H. pylori. Western blotting, qRT-PCR, immunofluorescence, immunohistochemistry and ELISA were utilized for functional and mechanistic studies. Single-cell RNA sequencing (ScRNA-seq) analysis of human gastric tissues, followed by validation, indicated that NLRP3 was primarily expressed in myeloid cells and was significantly increased in H. pylori-positive gastritis compared to H. pylori-negative gastritis. Infection with PMSS1 and NCTC11637 H. pylori strains induced NLRP3 inflammasome activation in vitro (THP1 cells) and in the insulin-gastrin (INS-GAS) transgenic mouse model. Deletion of NLRP3 in BMDMs showed marked inhibition of H. pylori-induced M1 macrophage polarization. Furthermore, NLRP3 inflammasome activation upon TNFα, or H. pylori stimulation, was partially blocked by TNFα/TNFR1 signaling inhibitors. Deletion of TNFR1 in BMDMs significantly impaired NLRP3 inflammasome activation and M1 macrophages induced by H. pylori. This study revealed that the activation of NLRP3 inflammasome, regulated by the TNF/TNFR1 signaling axis, is a key regulator of H. pylori-induced M1 macrophage activation and gastritis.